Empirical studies on determinants of IPO underpricing in Chinese Growth Enterprise market - SHEN, ZHUOCHEN (2016)
When first proposed the conception of IPO underpricing, this topic have sparked concerns. Various studies demonstrate that this phenomenon is widespread in global stock market. This dissertation reviews western theories and empirical studies towards Chinese stock market and other markets. Further, this study collects 317 samples of IPO shares from 2009 to 2012 and uses the multiple regression analysis method to test the determinants of IPO underpricing. The results present three primary factors for underpricing in growth enterprise market (GEM). The first is the information asymmetry caused by inefficient regulation. The second reason is the immature investment behavior. Investors in GEM and Chinese financial markets prefer speculation behavior. Third, the variables of special characteristics in Chinese stock market confirm that the inequity of supply and demand is still an issue after a series of IPO reforms.